Blockchain-Powered Fortification: Transformative Security Measures in Data Distribution Systems - Dikki Saputra Irawan (Institute of Computer Science (IOCS), 2023)
This research embarks on an exploration of the transformative role played by blockchain technology in fortifying the security landscape of data distribution systems. As the digital ecosystem evolves, the need for resilient and secure mechanisms becomes paramount. Our study unravels the multifaceted contributions of blockchain in this context, focusing on decentralization, immutability, smart contracts, collaborative trust, privacy features, resistance to unauthorized alterations, and the interplay of transparency, accountability, and trust. These findings not only redefine the paradigm of data security but also offer a roadmap for future research, suggesting avenues for scalability, interoperability, quantum-resistant measures, adaptive smart contracts, decentralized governance models, economic and environmental impact assessments, user experience enhancements, and cross-domain applications. As we navigate the digital frontier, this research signifies a transformative beacon, inviting further exploration into reshaping the foundations of secure data distribution in the dynamic landscapes of tomorrow.